MAPPING DATA DAN INFORMASI PADA KAWASAN PESISIR DAN ZONA PENYANGGA KAWASAN PESISIR - Mohammad Agung Ridlo (Prosiding Seminar Nasional Inovasi Dalam Pengembangan SmartCity, 2017)
AbstractLay out paln is scientifically consept that was created as a manual of the development realization. That is, in every discussion about development, lay out plan must be consistency obeyed as if dealt before.If only in its realization, there are any illegal or unsuitable actions about lay out plan, it can be said that improperly mechanism and process was happened along the development.In accordance with the statement above, this paper would try to discuss about fact finding in term of lay out’s problems in a certain city, then looked for its necessary expectation solutions. Basically, the lay outs problems in a certain city are intercorrelated problems, either externally and internally. In order to solve these problems, it may need willingness from all of  the stakeholders.Key Words: Lay out plan,  Hope, and Realization